PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI KOTA PAREPARE - Jumira, Jumira; Dangnga, Muhammad Siri; Nuryadin, Rusmin (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of workload and work environment on employee performance in Parepare City. The data collection techniques used in this study were interviews and questionnaires. The population in the study amounted to 46 people and a sample of 46 people. The data analysis technique in this study used multiple linear regression analysis techniques. From the results of this study, it is stated that the Workload variable (X1) has a positive and significant effect on Employee Performance (Y). And the Work Environment variable (X2) has a positive and significant effect on Employee Performance (Y). The research method used is distributing questionnaires to 46 employees who are respondents. This research is quantitative because the data generated is in the form of numbers, from which the data is processed using SPSS software.